Predicting Urea Hydrolysis in a Loblolly Pine Forest Floor. Issue 6 (19th September 2014) - Kissel, David E.; Cabrera, Miguel L.; Craig, Joseph; Ariyama, Jiro; Vaio, Nicolas; Rema, John
Abstract : In a pine forest, urea hydrolysis rates can vary widely. The rate of urea hydrolysis is controlled by the amount of urease enzyme, temperature, pH, urea concentration, but at the soil surface, soil water potential is an especially critical factor because it may vary widely in short periods of time due to precipitation, dews, and rapid evaporation. The objective of this study was to describe the quantitative relationship between soil water and urea hydrolysis rates in a loblolly pine ( Pinus taeda L.) forest floor. Hydrolysis rates were measured in a pine forest with time after urea was applied in seven studies performed at different times that varied widely in soil water content and temperature. Separately in a laboratory study, the urea hydrolysis rates were measured in pine needles and in the humified layer at different water potentials. Results showed that although well‐defined relationships were found between urea hydrolysis rates and forest floor water potentials, the urea hydrolysis rates measured in the field could not be predicted based on these relationships and the water potential of the forest floor pine needles at the time of urea application. However, the percent of urea hydrolyzed at 3 and 29 d could be predicted accurately from the initial water potential of new needles and an interaction between initial water potential and relative humidity days.